Estudo da técnica do imbricamento da parede livre do ventrículo esquerdo em cães (Canis familiaris Linnaeus, 1758) - Andrade, James Newton Bizetto Meira de (1999)
Orientador: Antonio Felipe Paulino de Figueiredo Wouk